(untitled) (Docentes 2.0 Journal, 2025)
Artificial Intelligence (AI) tools have increased academic production by facilitating the writing and analysis of texts through advanced language models. The overall objective was to identify business students’ perceptions of the usefulness of AI in scientific articles. This research was conducted within the pragmatic paradigm, employing a convergent mixed-methods approach, including convergent triangulation design, concurrent triangulation design, and a cross-sectional design. The sample consisted of 75 students from three private universities in Lima, who were administered an 18-item questionnaire designed by the researchers. A closed-ended survey was used to collect data. The analysis of the results was based on a thematic approach, highlighting students’ reflections on the usefulness of these tools in preparing scientific articles. The findings indicate that the use of AI tools reduces the level of effort. However, biases and unethical use exist that lead to poor originality and unreliable results in scientific articles. During the discussion, it was suggested that while AI tools are very helpful, certain factors may raise questions about their reliability. In conclusion, the authors highlight students’ perceptions of the usefulness of AI tools and how this could improve their effectiveness in optimizing the quality, reliability, and relevance of academic work.